Understanding adaptation to fluconazole: comparative insights into tolerance and resistance in Saccharomyces cerevisiae and Candida albicans - Lijun Zheng; Yubo Dong; Jing Wang; Yonghui Jia; Weifang Wang; Yi Xu; Yi Xu; Liangsheng Guo (Frontiers in Cellular and Infection Microbiology)
IntroductionAntifungal resistance and tolerance are distinct responses exhibited by fungi when exposed to drugs. While considerable research has focused on azole tolerance in the human pathogen Candida albicans, studies in other fungal species remain limited.ObjectiveThis study aims to conduct a comparative investigation of the adaptation of the model organism Saccharomyces cerevisiae and C. albicans to fluconazole in vitro.MethodsWe performed experiments using laboratory strains of S. cerevisiae and C. albicans to evaluate their fluconazole tolerance and resistance under varying temperature conditions. High concentrations of fluconazole were administered, and subsequent changes in fungal phenotypes were analyzed through techniques such as transcriptome analysis and monitoring of petite formation.ResultsOur results revealed that fluconazole tolerance is present in wild-type strains of S. cerevisiae and is influenced by temperature, albeit in a manner opposite to that observed in C. albicans. Importantly, when subjected to high concentrations of fluconazole, S. cerevisiae strains developed resistance without displaying tolerance; all resistant adaptors identified were petites. Chemical induction of petite formation led to an increase in resistance accompanied by a decrease in tolerance.ConclusionTranscriptome analysis indicated that petites up-regulated efflux mechanisms while down-regulating most ERG genes. This suggests that, unlike petite-negative C. albicans, petite-positive S. cerevisiae swiftly transitions to a petite phenotype upon exposure to fluconazole, resulting in enhanced resistance but diminished tolerance. This evolutionary divergence emphasizes the need for additional studies on fluconazole tolerance in other pathogenic fungi.